Effects of transverse air flow on mass loss rate of alcohol pool fires in an inclined wind tunnel - Tao, Changfa; Wang, Xishi; Zhang, Xiaonan (Journal of Civil Engineering and Management, 2015)
In order to study the effects of inclined wind direction on combustion characteristics of alcohol pool fires, an inclinable wind tunnel was developed and used for providing venting wind with different directions. The wind tunnel can be sloped from 0° to 30° while the fuel pan is kept horizontal inside the tunnel. The wind speed can be altered from 0 to 3.0 m/s. The mass burning rate of square, rectangular and circular alcohol pool fires under different wind direction have been studied experimentally. The results show that the mass burning rate increases faster with increasing the slope angle of the wind tunnel and increasing the downstream edge length of the pool.